Recovery process of murabahah financing in islamic financial institutions in Malaysia - Siti Mazlita Yamaludin (Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2014)
A scenario of recovery in Islamic banking industry is one of the vital sections in banking nowadays since it is actually to minimize the arrears and non-performing financing (NPF) as well as to generate profit to the banks. For this purpose of research, the writer examines the reality of recovery process in Islamic financial institutions by focusing on the Murabahah financing. Based on current practices, a major problem associated with Murabahah financing related to a possibility of default by customers. The longer it took the customer to pay the payment, the higher is the Murabahah price. If the customers pay the higher profit rate will have the larger probability of default. Therefore, the Islamic financial institutions will definitely use any possible ways to recover back the money fkom the defaulters. However, there are some issues with regards to the process of recovery from Shari'ah point of views including late payments fee or compensation (ta'widh), penalty (gharamah), early payment (ibra') as well as the rescheduling and restructuring of the financing. This research attempts to discuss these issues based on the Guidelines issued by Central Bank of Malaysia (BNM) while comparing these to the practice in Islamic financial institutions in Malaysia. From the findings of the research and the analysis of the sample documents, it is concluded that the current recovery process of Murabahah financing in Islamic financial institutions in Malaysia is slightly same as per standard practice of recovery process in other financing in Malaysia. Additionally, this research finds that the impositions of ta'widh upon defaulters is relevant in the industry to compensate the actual costs incurred by Islamic financial institutions as well as the penalty (ghavamah) as deterrent for defaulters against delays in payment. Both charges and penalty do not constitute riba' as compared to the conventional practice and considered as Shari'ah compliance practice. With respect to the issues of ibra' on early settlement due to default cases, the latest Guideline on Ibra' (Rebate) for Sale- Based Financing issued by BNM is a good initiative to eliminate uncertainties pertaining to customer's right in receiving ibra' from Islamic financial institutions and apply it in their claim in court. However, the writer hoped that the regulators will issue the Shari'ah parameter on recovery process of each products offered in Malaysia including the restructuring and rescheduling method to make it as a standard practices in the industry.